The Effect of Live Commerce and Entrepreneurial Marketing on Purchasing Decisions for MSME Products in Bengkulu City - Heskyel Pranata Tarigan; Vettica Diana Saputri (Jurnal Kewirausahaan & Inovasi, 2026)
The rapid adoption of social commerce has created a new marketing space for micro, small, and medium enterprises (MSMEs), yet local sellers still face challenges in converting digital interaction into actual purchases. This study examines the effects of live commerce and entrepreneurial marketing on purchasing decisions for MSME products in Bengkulu City. A quantitative explanatory survey design was used with 200 consumers selected through purposive sampling based on experience watching live-selling sessions and purchasing local MSME products. Data were measured using a five-point Likert scale and analyzed with validity and reliability tests, descriptive statistics, multiple linear regression, t tests, F test, and the coefficient of determination. The illustrative processed dataset shows that live commerce has a positive and significant effect on purchasing decisions (b = 0.521; p < 0.001), while entrepreneurial marketing also has a positive and significant effect (b = 0.437; p < 0.001). Simultaneously, both variables explain 63.5% of the variance in purchasing decisions. The findings indicate that real-time interaction, product demonstrations, opportunity-driven marketing, innovation, customer intensity, and value creation can strengthen consumer confidence and accelerate purchase decisions for local MSME products